THE INFLUENCE OF EMOTIONAL INTELLIGENCE, SPIRITUAL INTELLIGENCE, INTELLECTUAL INTELLIGENCE ON THE PERFORMANCE OF PRIMARY IQRO COOPERATIVE EMPLOYEES (PRIMKOPIQ) - Iswadi, Udi; Dzikri, Ahlu; Aprilliadi, Teddy (Jurnal Manajemen, 2024)
This study aims to determine the effect of emotional intelligence, spiritual intelligence, intellectual intelligence on the performance of employees of Primary Cooperative Iqro (PRIMKOPIQ). The variables used are emotional intelligence, spiritual intelligence, intellectual intelligence as independent variables, and employee performance as dependent variables. The research method used in this study is the survey method, while the population in this study are employees of Primary Cooperative Iqro (PRIMKOPIQ). The number of samples determined in this study was 37 respondents. Sampling was carried out by taking the entire population. The data analysis technique used was multiple correlation analysis and determinant coefficient (R2). The results of the coefficient analysis show that the t-test of the emotional intelligence variable has a positive and significant effect on performance (t count 2.087> t table 2.034), the spiritual intelligence variable on performance shows a positive and significant effect (t count 4.604> t table 2.034), the intellectual intelligence variable on performance shows a positive and significant effect (t count 2.089> t table 2.034), and the emotional intelligence, spiritual intelligence and intellectual intelligence variables simultaneously have a significant effect on the performance of Primary Koperasi Iqro (PRIMKOPIQ) employees. This is based on the results of the f-test with an ftable value of 3.27 while the fcount value is 14.701.